Preferensi Konsumen Menentukan Tingkat Adopsi Petani Terhadap Varietas Padi di Provinsi Sumatera Barat - Wahyu Wibawa (Jurnal Pembangunan Nagari, 2022)
New Superior Varieties (VUB) are innovations that can increase rice production. The objectives of this research are to: (1) Collect data and information related to consumer preferences and VUB adoption rates. (2).Develop recommendations to accelerate the adoption of VUB. This research methodology was carried out by collecting data through literature studies and collecting secondary data from various related agencies. The results of the study show that many factors influence the adoption rate of VUB. The spread and adoption of VUB is very low due to its characteristics which do not match the preferences of farmers and consumers. The texture and taste of rice are the main factors and determine the preferences of rice consumers in West Sumatra. The acceleration of VUB adoption needs to be supported by increasing the intensity and quality of extension. The conclusion from the study is that there is a close relationship between consumer preferences and VUB adoption in rice farming. Prioritizing productivity improvements without considering consumer preferences could hinder VUB's adoption goals. Specific VUB needs to be immediately created and supported with a reliable extension strategy. Recommendations to increase VUB adoption are: (1) Balitbangda collaborated with research institutions or university to create specific VUB by utilizing local varieties as parents. (2) Increasing extension performance to educate farmers intensively. (3) The agriculture office helps provide specific VUB seeds to farmers. (4) Methods of dissemination and extension to farmers need to be perfected.